STOMATITIS APTHOSA REKUREN (SAR) MINOR MULTIPLE PRE MENSTRUASI (Laporan Kasus) - Amelia Thantawi; Khairiati .; Mela Meri Nova; Sri Marlisa; Abu Bakar (ODONTO : Dental Journal, 2014)
Recurrent aphthous stomatitis (RAS) is an inflammation of the soft tissues of the mouth that is characterized by recurrent ulcers. SAR is clinically divided into three types, ie recurrent aphthous stomatitis minor, major and herpetiform. Clinical features of minor types usually with a diameter of about 2-4 mm with yellow-gray base and surrounded by an erythematous halo, affects mainly the non-keratinized mobile mucosae such as lips and tongue, a few ulcers (1-5) or multiple at a time, minor ulcers usually heal within 10-14 days without scarring. Early lesions on the SAR is usually felt by people as burning, followed by extremely pain. The aetiology of RAS is unknown, but associated with a variety of predisposing such as menstrual cycle and trauma. Case management is topical steroids, topical antiseptic and vitamins C to relieve the symptoms and fasten healing.